A pH-sensitive supramolecular nanosystem with chlorin e6 and triptolide co-delivery for chemo-photodynamic combination therapy - Yihan Wu; Jingjing Li; Xuemei Zhong; Jinfeng Shi; Yanfen Cheng; Chenglin He; Jiaxin Li; Liang Zou; Chaomei Fu; Meiwan Chen; Jinming Zhang; Huile Gao (Elsevier, 2022)
The combination of Ce6, an acknowledged photosensitizer, and TPL, a natural anticancer agent, has been demonstrated as a useful strategy to reinforce the tumor growth suppression, as well as decrease the systemic side effects compared with their monotherapy. However, in view of the optimal chemo-photodynamic combination efficiency, there is still short of the feasible nanovehicle to steadily co-deliver Ce6 and TPL, and stimuli-responsively burst release drugs in tumor site. Herein, we described the synergistic antitumor performance of a pH-sensitive supramolecular nanosystem, mediated by the host-guest complexing between β-CD and acid pH-responsive amphiphilic co-polymer mPEG-PBAE-mPEG, showing the shell-core structural micelles with the tight β-CD layer coating. Both Ce6 and TPL were facilely co-loaded into the spherical supramolecular NPs (TPL+Ce6/NPs) by one-step nanoprecipitation method, with an ideal particle size (156.0 nm), acid pH-responsive drug release profile, and enhanced cellular internalization capacity. In view of the combination benefit of photodynamic therapy and chemotherapy, as well as co-encapsulation in the fabricated pH-sensitive supramolecular NPs, TPL+Ce6/NPs exhibited significant efficacy to suppress cellular proliferation, boost ROS level, lower MMP, and promote cellular apoptosis in vitro. Particularly, fluorescence imaging revealed that TPL+Ce6/NPs preferentially accumulated in the tumor tissue area, with higher intensity than that of free Ce6. As expected, upon 650-nm laser irradiation, TPL+Ce6/NPs exhibited a cascade of amplified synergistic chemo-photodynamic therapeutic benefits to suppress tumor progression in both hepatoma H22 tumor-bearing mice and B16 tumor-bearing mice. More importantly, lower systemic toxicity was found in the tumor-bearing mice treated with TPL+Ce6/NPs. Overall, the designed supramolecular TPL+Ce6/NPs provided a promising alternative approach for chemo-photodynamic therapy in tumor treatment.